Heritability and genetic advancement on agronomic characters of Toraja red rice x Inpari-4 white rice genotypes - Y L Limbongan; Driyunitha DRIYUNITHA; Rinaldi Sjahril; MUH. RIADI; IRMA JAMALUDDIN; ANDI MULIANI OKASA; NURHAYA J. PANGA (Society for Indonesian Biodiversity, 2021)
Abstract. Limbongan YL, Driyunitha, Sjahril R, Riadi M, Jamaluddin I, Okasa AM, Panga NJ. 2021. Heritability and genetic advancement on agronomic characters of Toraja red rice x Inpari-4 white rice genotypes. Biodiversitas 22: 3446-3451. Determination of genetic diversity, heritability, and genetic advance on specific agronomic characters of cross-breed red rice genotypes (Toraja red rice Pare Lea’ x Inpari-4) was done in Tallunglipu, North Toraja, South Sulawesi, Indonesia. The experiment was designed using a randomized complete block design. Twenty-one days old seedlings were transplanted following the system of rice intensification practices. Selection was conducted at F2 as a novel method to speed up genetic advancement and ensure progeny production with desired agronomic traits. Results indicated existence of a considerably high level of diversity among genotypes tested, where the highest value for genetic advance was observed in filled-grain weight per hill of F2 plants (983.890), followed by plant height (335.124), and filled-grain weight per hill of F1 (306.645). The highest estimate of broad-sense heritability was recorded in 1000-grain weight (0.915), number of productive tillers (0.788), plant height (0.765), flag leaf length (0.705), filled-grain weight per hill (0.688), and harvest age (0.594). Genetic advance of agronomic characters between genotypes varied from 1.631-38%, where the highest estimate was recorded in filled-grain weight per hill (38%) and plant height (24.648%). The above-mentioned characters could be used for selection in further rice breeding programs to obtain plants with superior genotypes.